Stress-strain behavior of concrete block masonry prisms under compression - Mohamad, Gihad (2012)
The aim of this work is to critically assess a stress-strain model using experimental masonry prisms constructed from different blocks and mortar. The following conclusion may be drawn from this work: mortar is mostly responsible for the non-linear behavior of masonry. The initial tangent modulus, obtained taking into account the compressive strength, provides a strongly non-linear relationship between elasticity modulus and compressive strength.